Analisis Trust, Perceived Risk, Dan Perceived Ease Of UseTerhadap Keputusan Pembelian Secara Elektronik(Survei Pada Komunitas OLX Regional Solo) - Heri Setiawan, Puguh; , Dr. Triyono, SE, M.Si (2016)
Decision making in electronic purchasing is very risky to consumers, therefore consumers must to be careful with the seller integrity with the risks which are guaranteed. This research is aim to analyze are the consumers benefit, the risk s and the perceived of use e-commerce. The method of this research was using descriptive quantitative approach. The data which is used in the research is primer data from questioner by disseminating to OLX solo community. Instrumen to analyze the data in this research by using multiple linear regression analysis. The result of this research are indicate that (1) The consumers benefit have positive effect toward electronic purchasing decision. (2) The risk of online purchasing have negative effect toward electronic purchasing. (3) The perceived ease of use electronic purchasing have positive effect toward electronic purchasing.